Current status of herbal product: Regulatory overview - Sanjay Sharma (Wolters Kluwer Medknow Publications, 2015)
A review of the regulatory status of herbal drugs/products was done for few countries forming part of Asia, Africa, America, Europe, and Australia, to understand various categories under which the trade of herbal products is permitted and their premarketing requirements. A critical assessment was done, to know the hindrances in the process of harmonization of herbal products. It has been found that there is a lack of harmonization in the regulatory requirements of herbal products internationally, besides the issues of availability of herbs and their conservation. These are hindering the international trade and growth of the herbal products segment.